ОРГАНІЗАЦІЯ ВИРОБНИЦТВА ПРОДУКЦІЇ РОСЛИННИЦТВА В ПОМІЩИЦЬКИХ ГОСПОДАРСТВАХ ЛІВОБЕРЕЖНОЇ УКРАЇНИ ПІСЛЯ СКАСУВАННЯ КРІПОСНОГО ПРАВА (1861-1917 РР.) (Zaporizhzhia Historical Review, 2021)
In this article the questions about organization of production of plant’s products in the landowner farming in the left-bank Ukraine after repeal of serfdom (1861-1917): plots, the sowing structure, the order of sowing, peculiarities of production on the macro- and micro level – are analyzed.